2021
DOI: 10.3390/cells10092438
|View full text |Cite
|
Sign up to set email alerts
|

All Roads Lead to Rome: Different Molecular Players Converge to Common Toxic Pathways in Neurodegeneration

Abstract: Multiple neurodegenerative diseases (NDDs) such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS) and Huntington’s disease (HD) are being suggested to have common cellular and molecular pathological mechanisms, characterized mainly by protein misfolding and aggregation. These large inclusions, most likely, represent an end stage of a molecular cascade; however, the soluble misfolded proteins, which take part in earlier steps of this cascade, are the more toxic players. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 373 publications
(456 reference statements)
1
12
0
Order By: Relevance
“…iPSCs and co-cultures are potentially beneficial to incorporate critical controllers of neuronal health into ALS studies. This involvement of non-neuronal cell types is consistent with the non-cell-autonomous theory that challenges the cell-autonomous theory (Chen et al, 2018;Argueti-Ostrovsky et al, 2021).…”
Section: Amyotrophic Lateral Sclerosis Molecular and Genetic Characte...supporting
confidence: 81%
“…iPSCs and co-cultures are potentially beneficial to incorporate critical controllers of neuronal health into ALS studies. This involvement of non-neuronal cell types is consistent with the non-cell-autonomous theory that challenges the cell-autonomous theory (Chen et al, 2018;Argueti-Ostrovsky et al, 2021).…”
Section: Amyotrophic Lateral Sclerosis Molecular and Genetic Characte...supporting
confidence: 81%
“…A range of cellular processes are reported to influence liability for the most common motor neuron disease, ALS. These include aberrant RNA processing, ER stress, metabolic abnormalities, neuroinflammation, oxidative damage, and mitochondrial dysfunction, among others 61 . As with many neurodegenerative conditions, age is the primary risk factor for ALS, and there is clear overlap between pathways implicated in the disease and natural aging processes 62 .…”
Section: Discussionmentioning
confidence: 99%
“…These vacuoles are most likely swollen mitochondria, with the involvement of aggregated mutant SOD1 for their appearance [ 20 , 21 , 38 ]. Since pathologic aggregation of proteins is considered a main reason for neurodegeneration in general [ 39 ], and SOD1-related neurodegeneration in ALS in particular [ 40 ], reductions in the severity of this process may be the underlying reason for our observed protection against trigeminal motor neuron loss. We also showed that MRI analysis of the trigeminal and facial motor nuclei recapitulated human SOD1-related vacuolization.…”
Section: Discussionmentioning
confidence: 99%